Challenges of Measuring a Faculty Member Activity in Medical Schools - Mohammadi, A (Kowsar, 2011)
BACKGROUND: One of the features of Mission Based Management is measuring the activities of faculty members and departments and their contributions to the school's mission. As it is important to assess the school's readiness for such a system, in this study we assessed the view points of Tehran Medical School's department chairs about faculty members’ activities. METHODS: We used focus group technique to identify participants' view points. We divided 30 department chairs into homogenous groups of 4-6. After a brief introduction, the moderator presented questions to determine the participants' idea and a secretary recorded them. We categorized view points into main themes and subthemes. RESULTS: Ninety three percent of chairs participated in the sessions. Department chairs' view points were categorized into 3 main themes: "system is effective and important", "system is effective and important but some challenges should be considered" and "system is ineffective and should not be implemented". Subthemes included chairs' concerns, views, fears and reasons. CONCLUSIONS: The results of the study provided reliable information about department chairs' concerns and reactions to this system. Finally, we determined points of strengths and anticipated threats for developing a faculty member activity measurement system.